Not dead yet: Diatom resting spores can survive in nature for several millennia. Issue 1 (7th January 2022) - Sanyal, Anushree; Larsson, Josefine; van Wirdum, Falkje; Andrén, Thomas; Moros, Matthias; Lönn, Mikael; Andrén, Elinor
Abstract: Premise: Understanding the adaptive capacities of species over long timescales lies in examining the revived recent and millennia‐old resting spores buried in sediments. We show for the first time the revival, viability, and germination rate of resting spores of the diatom Chaetoceros deposited in sub‐seafloor sediments from three ages (recent: 0 to 80 years; ancient: 1250 (Medieval Climate Anomaly) and 6600 (Holocene Thermal Maximum) calendar year before present. Methods: Recent and ancient Chaetoceros spores were revived to examine their viability and germination rate. Light and scanning electron microscopy and Sanger sequencing was done to identify the species. Results: We show that 6600 cal. year BP old Chaetoceros resting spores are still viable and that the vegetative reproduction in recent and ancient resting spores varies. The time taken to germinate is three hours to 2 to 3 days in both recent and ancient spores, but the germination rate of the spores decreased with increasing age. The germination rate of the recent spores was 41% while that of the ancient spores were 31% and 12% for the 1250 and 6600 cal. year BP old resting spores, respectively. Based on the morphology of the germinated vegetative cells we identified the species as Chaetoceros muelleri var. subsalsum . Sanger sequences of nuclear and chloroplast markers identified the species as Chaetoceros muelleri . Conclusions: We identify a unique model system, Chaetoceros muelleri var . subsalsum and show that recent and ancient resting spores of the species buried in sediments in the Baltic Sea can be revived and used for long‐term evolutionary studies.